Intraoperative Consultation (Frozen Section) in the Diagnosis of Ovarian Tumour (Bangladesh Medical Journal, 2021)
Ovarian cancer is a devastating disease preoperative evaluation of the patients with an ovarian tumour is difficult. So frozen section biopsy of ovarian tumour is important to determine the extent of surgery. This retrospective cross-sectional study was carried out in the Department of Gynaecological Oncology, Bangabandhu Sheikh Mujib Medical University from August 2016 to July 2017 to determine the validity of frozen section biopsy in the diagnosis of ovarian tumour. Fifty cases of ovarian tumour underwent frozen section biopsy were included by purposive sampling. Histopathological finding was taken as the gold standard. Data was analyzed by SPSS version 16. The sensitivity of frozen section in the diagnosis of benign, borderline and malignant were 100%, 100% and 97.67% respectively as well as the specificities were 100%, 97.96% and 100% respectively. Similarly the accuracy, PPV, NPV for the benign, borderline and malignant ovarian tumour were also high except the borderline tumour which had low PPV.Bangladesh Med J. 2019 Sep; 48 (3): 34-38